Glucose control in pediatric intensive care unit patients using an insulin-glucose algorithm - Wintergerst, Kupper A; Deiss, Dorothee; Buckingham, Bruce; Cantwell, Martin; Kache, Saraswati; Agarwal, Swati; Wilson, Darrell M; Steil, Garry (Diabetes technology & therapeutics, 2007)
Control of hyperglycemia in adult medical and surgical intensive care units (ICUs) has been shown to dramatically decrease morbidity and mortality. Algorithms to achieve glycemic control in the ICU setting are evolving. We have evaluated the use of a discrete proportional-integral-derivative (PID) algorithm to control hyperglycemia in pediatric ICU (PICU) patients both with and without diabetes. Six PICU patients [four with diabetic ketoacidosis (DKA) and two with glucocorticoid-induced hyperglycemia] with glucose values >150 mg/dL were enrolled. Their hyperglycemia was managed with a PID algorithm that provided recommendations for both changes in the intravenous insulin infusion rate and the time to obtain the next discrete glucose value. Glucose targets were adjusted based on clinical circumstances. Patients (mean age 9.2 years; range 1.8-14 years) utilized the algorithm for a total of 454.4 h. Mean time to the initial glucose target was 8.7 h (range 1.3-15.1 h) in five patients. One subject with hyperosmolar DKA did not achieve target before discharge from the PICU, and another was at target when the algorithm was initiated. After the glucose target was achieved, the mean SD was 23.5 mg/dL, and glucose values were >40 mg/dL above target 13% of the time and <40 mg/dL below target 1% of the time. There were no glucose values <55 mg/dL. The PID algorithm safely and effectively controlled hyperglycemia in a PICU, despite multiple changes in intravenous fluids, steroid doses (including high-dose pulses), and hemodialysis.